Insistent life : principles for bioethics in the Jain tradition - Donaldson, Brianne; Bajželj, Ana, 1981- (University of California Press, 2021)
"Insistent Life is the first full-length interdisciplinary treatment of the foundational principles and principles of application for engaging contemporary bioethics within the Jain tradition. The book fills a significant gap in both the fields of bioethics and Jain studies since Jainism, perhaps more so than any other South Asian tradition, is strongly focused on the ethics of birth, life, and death, with regard to humans as well as other living beings. Brianne Donaldson and Ana Bajželj analyze a diverse range of Jain texts and contemporary sources on Jain doctrines and practices, alongside bioethics, to identify Jain perspectives on bioethical issues while highlighting the complexity of their personal, professional, and public dimensions. The book also features extensive original data--represented in visual graphs--based on an international survey the authors conducted with Jain medical professionals in India and diaspora communities of North America, Europe, and Africa"--